Caracterização da fase cristalina dos antivirais efavirenz e oseltamivir por RMN e cálculos teóricos - Rodrigues, Diego Alves (2014)
The commercialization of drugs most often occurs through their solid forms, and the caracteriscas of drugs should be kept throughout the process of production and storage. Upon this fact the characterization studies of the drugs in the solid state are in constant growth. NMR solid state high resolution can provide important complementary information current techniques, through the changes of the chemical shifts.The objective of this study is the characterization of the drug efavirenz (EVZ) and oseltamivir by the technique of nuclear magnetic resonance both in solution and solid state data together with the theoretical computations. Efavirenz drug was characterized by X diffraction (XRD), nuclear magnetic resonance in solution (1H NMR and 13C {1H}) and solid (CPMAS NMR and 13C CPTOSS e15N), and the use of theoretical calculations in solution GIAO using the model for unambiguous assignment of NMR signals. The same techniques of structural characterization and theoretical calculations were used in drug Oseltamivir, reeking the technique of X diffraction (XRD), and this drug hitherto considered amorphous.The experimental data obtained by NMR analyzes were consistent with the structure of drug efavirenz and oseltamivir; and the results of theoretical calculations were tabulated, a work of statistical analysis is performed in order to correlate the experimental data with the theoretical data, the analysis of the standard deviation (SD), mean deviation (MD), linear coefficient (R) . Notably, the theoretical values of the chemical shifts of 1H and 13C NMR in solution, obtained at the level of theory DFT/B3LYP, allowed for the drugs in question a considerable correlation with experimental values and permitted to associate a low computational cost of a good precision results.Thus using NMR experiments in solution 1D and 2D allies the results of computational theoretical calculations was possible the elucidation and assignment of all NMR signals of 1H and 13C of both drugs. efined experiments 1D solid state NMR (CP / TOSS and 13C CP / MASS de15N) allowed identification of these atoms in the solid state. Combined with theoretical calculations GIPAW provided valuable information on the molecules within the asymmetric unit of each drug.